HUBUNGAN LAMANYA PEMAKAIAN KB SUNTIK 3 BULAN TERHADAP GANGGUAN HAID DI UPT PUSKESMAS KECAMATAN PLAMPANG - Susi Susanti; Galuh Permatasari; Yunita Lestari (Jurnal Kesehatan dan Sains, 2021)
Family Planning (KB) is an attempt to distance or plan the number and distance of pregnancy by using contraception. The results of a preliminary study conducted at plampang district health center in January-March 2020 as many as 103 respondents.From the data researchers interviewed as many as 39 respondents and found problems that occurred in plampang district health center that is delayed menstruation for 6 months to 1 year due to using injectable birth control 3 months. The purpose of this study was to see if there was a relationship in the duration of use of injection control 3 months to menstrual disorders. The method used in research is descriptive analytics with a cross sectional approach using primary and secondary data.The results of the study of 39 respondents of kb acceptors injected 3 months in UPT Puskesmas Plampang District in 2020 which was processed with SPSS 20 found 23 respondents with the use of injectable birth control 3 months with a long use of > 6 months found 16 (64.8%) respondents who experienced menstrual disorders while new use < 6 months there were as many as 7 (27.5%) respondents who experienced menstrual disorders that showed a significant relationship between the length of use of 3 months injectableKB against menstrual disorders in Plampang village of Plampang District of Sumbawa Regency with a value of p (sig)<a (0.303 < 0.05). Concluded that there is a relationship between the length of use of injectable birth control 3 months and menstrual disorders.